MATERNAL DEPRIVATION AND SPIRITUAL RESILIENCE IN THE SECRET LIFE OF BEES: A PSYCHOANALYTIC PERSPECTIVE THROUGH ATTACHMENT THEORY - Maharani, Ayu; Margawati, Prayudias (Lire Journal (Journal of Linguistics and Literature), 2025)
Maternal care plays a critical role in shaping the emotional and psychological development of human being’s early life.  The absence of maternal care, can lead to long-term challenges, including emotional dysregulation, low self-esteem, and difficulty forming secure attachments. Maternal deprivation refers to the lack of adequate maternal care and emotional support during a child’s early developmental stages. This research examines the effects of maternal deprivation and the development of psychological resilience as portrayed in Sue Monk Kidd’s novel The Secret Life of Bees. Through John Bowlby’s Attachment Theory, the research explores how early maternal absence impacts the protagonist, Lily Owens, and her emotional development. The analysis highlights how maternal deprivation manifests through Lily’s struggles with self-worth, trust issues, and emotional regulation. Despite these challenges, the novel also presents a narrative of resilience, as Lily finds surrogate maternal figures and healing through meaningful connections. The concept of psychological resilience, examined through the lens of trauma psychology, illustrates how Lily’s adaptive coping mechanisms help mitigate the adverse effects of maternal loss. The research integrates psychoanalytic literary criticism to analyze how the symbolic maternal figures in the novel support Lily’s journey toward healing. This research contributes to a deeper understanding of the psychological implications of maternal deprivation and the role of resilience in overcoming early childhood trauma, offering valuable insights for both literary and psychoanalytic studies.